1999
DOI: 10.1159/000028280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Binding Sites of Bopindolol and Its Two Metabolites with β<sub>1</sub>-Adrenoceptors by Molecular Modeling: Comparison with β<sub>2</sub> Adrenoceptors

Abstract: This study was designed to examine the importance of interaction in the bindings of nonselective β-blockers to β1-adrenoceptors (β1-ARs) as compared with β2-ARs, using molecular modeling. The β-blockers used in this study were bopindolol [4-(benzoyloxy-3-t- butylaminopropyl)-2-methylindol hydrogen malomate], its two metabolites [18-502 – hydrolyzed bopindolol or 4-(3-t-butylamino-2-hydroxypropoxy)-2-methyl indole – and 20-785 – 4-(3-t-butylaminopropoxy)-2-carboxyl indole], and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…These authors also indicated that derivatization of TM6 and TM7 by these photolabelled compounds suggests the folded conformation of these compounds in the ligand binding pocket. On the other hand, our laboratory deduced 3D structures of human >-ARs and profiles of >-AR antagonists binding by computer simulation based on the electron density map of rhodopsin (34,35). This modeling analysis supported the results of molecular biological-/pharmacological-experiments and further gave us some novel interesting suggestions.…”
Section: Analysis Of Binding Sites In > > > >-Ar Subtypes By Moleculamentioning
confidence: 52%
See 1 more Smart Citation
“…These authors also indicated that derivatization of TM6 and TM7 by these photolabelled compounds suggests the folded conformation of these compounds in the ligand binding pocket. On the other hand, our laboratory deduced 3D structures of human >-ARs and profiles of >-AR antagonists binding by computer simulation based on the electron density map of rhodopsin (34,35). This modeling analysis supported the results of molecular biological-/pharmacological-experiments and further gave us some novel interesting suggestions.…”
Section: Analysis Of Binding Sites In > > > >-Ar Subtypes By Moleculamentioning
confidence: 52%
“…This modeling analysis supported the results of molecular biological-/pharmacological-experiments and further gave us some novel interesting suggestions. We assumed that the amine, benzoic acid, indole methyl, (TM5) and Pro 236 (TM5) of >1-AR, respectively, by either hydrogen bonding or hydrophobic interactions (35). Thus, the analysis of interaction between ligands and receptors by this computer simulation will give us newer information of highly and more precise 3D structures of >-AR subtypes and/or different interactions in these subtypes.…”
Section: Analysis Of Binding Sites In > > > >-Ar Subtypes By Moleculamentioning
confidence: 99%
“…The functional groups of propranolol and bopindolol involved in interactions with ß-ARs were amino, benzoic, indole methyl, naphthyl, isopropyl, t-butyl alcohol and indole ring groups, and these Nakamura/Suzuki/Ohnuki/Hattori/ Watanabe/Kurose/Nagao/Nagatomo functional groups may interact with several amino acid residues in helices 3, 4, 5 and 6 of ß 1 -and ß 2 -ARs. Our previous studies [1,2] using molecular modeling also suggested that these functional groups of propranolol possibly interact with Try134, Ala343, Phe340, Pro339, Val137, Cys336, Asp138, Leu237 and Ser190 in transmembrane helices 3, 4, 5 and 6 of ß 1 -ARs. These studies suggested that these amino acid residues in each helix of ß 1 -ARs may be important for binding with ligands and for manifestation of ß-blocking actions.…”
Section: Discussionmentioning
confidence: 87%
“…Previously [1,2] we hypothesized that some functional groups of ß-blockers, the basic chemical structure of which is that of aryloxypropanolamine, are very important for interactions with amino acids in the seven transmembrane helices of ß-ARs. The functional groups of propranolol and bopindolol involved in interactions with ß-ARs were amino, benzoic, indole methyl, naphthyl, isopropyl, t-butyl alcohol and indole ring groups, and these Nakamura/Suzuki/Ohnuki/Hattori/ Watanabe/Kurose/Nagao/Nagatomo functional groups may interact with several amino acid residues in helices 3, 4, 5 and 6 of ß 1 -and ß 2 -ARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation